Способ увеличения выхода фторполимерных порошков при термическом переделе отходов политетрафторэтилена - Андреев А. А. Артем Андреевич; Бузник В. М. Вячеслав Михайлович; Дьяченко А. Н. Александр Николаевич; Кантаев А. С. Александр Сергеевич (2012, 2012)
Заглавие с экрана